Consultations by Asylum Seekers: Recent Trends in the Emergency Department of a Swiss University Hospital. - Martin Müller; Karsten Klingberg; David Srivastava; Aristomenis K Exadaktylos (PLoS ONE, 2016)
Background Large-scale war-related migration to Switzerland and other European countries is currently challenging European health systems. Little is known about recent patterns and trends in Emergency Department (ED) consultations by Asylum Seekers (AS). Methods A retrospective single-centre analysis was performed of the data from all adult patients with the official status of "Asylum Seeker" or "Refugee" who consulted the ED of Bern University Hospital, Switzerland, between June 2012 and June 2015. Patient characteristics and clinical information, such as triage category, type of referral and discharge, violence-related injury and diagnostic group on discharge, were extracted from the computerised database or determined from the medical reports. Changes in categorical variables between the three studied years were described. Results A total of 1,653 eligible adult patients were identified in the 3-year period. Between the first (06/12-06/13) and third periods (06/14-06/15), the number of presentations per year increased by about 45%. The AS came from 62 different nations, the most common countries being Eritrea (13%), Somalia (13%) and Syria (11%). The mean age was 33.3 years (SD 12.3) and two thirds (65.7%) were male. The proportion of women increased over time. Moreover the relative proportions shifted from patients between 20 and 50 years to patients of under 20 or over 60 years. Nearly two thirds of the patients were walk-in emergencies and this proportion increased over time. The mean triage score was 2.9 (SD 0.7), with more than 90% presenting as "urgent consultation". About half of the patients were treated for trauma (17.2%), infections (16.8%) or psychiatric problems (14.2%). Trauma was seen in a higher proportion of male than female patients. About 25% of the patients were admitted for in-hospital treatment. Conclusions The recent rise in AS in the population has lead to an increase in AS presenting to EDs. This changes the composition of ED patients and should raise awareness that changes in procedures may be needed. Infectious diseases and psychiatric problems remain a heavy burden for AS presenting in the ED. A trend towards an increasing proportion of walk-in patients to the ED could not be explained by this study. Further studies and surveillance are needed to investigate this trend.